The Use and Uniqueness of Parallelisms in the Poems of Ulugbek Hamdam (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the unique use of parallelism in the poetry of Ulugbek Hamdam, a prominent representative of modern Uzbek literature. The study focuses on the structural, semantic, and symbolic dimensions of parallelism, highlighting how these poetic tools are used to express philosophical, emotional, and national themes. Through a close analysis of the poem “I Planted Flowers...”, the research identifies various forms of parallelism—between human and nature, dream and reality, survival and creativity, homeland and flowers, as well as effort and outcome. The poet’s use of repeated imagery and mirrored syntax creates a harmonious interplay between form and meaning, rooted in Eastern literary traditions yet enriched by contemporary sensibilities. The article concludes that Hamdam's mastery of parallelism elevates his poetic voice, blending personal and universal elements into a deeply expressive, nationally conscious poetics.